Institutions, colonisation and the economic development of Western Australia and South Australia, 1829 to 1900 - O'Connell, Darren Christopher (Curtin University, 2014)
Douglass North's institutional framework is employed in this thesis to explain the disparate rates of economic growth between colonial Western Australia and South Australia. The differences in colonisation affected the design of institutions subsequently transferred to these colonies which had more of an impact of development than previously thought. By 1900, both colonies had roughly equal growth rates but this convergence only eventuated after Western Australia eliminated the worst deficiencies resulting from its foundation and reformed its institutional matrix.